Kapabilitas Santri Dalam Pencapaian Hasil Pembelajaran Pada Kelas Excellent di Pondok Pesantren Al-Ittifaqiah Indralaya Sumatera Selatan - Muyasaroh, Muyasaroh; Herlina, Herlina (MISYKAT: Jurnal Ilmu-ilmu Al-Quran Hadist Syari'ah dan Tarbiyah, 2023)
In an effort to develop quality alumni, Islamic boarding schools have implemented learning innovation programs by forming several Excellent classes that offer exclusive programs compared to Regular class types. For example, the Al-Ittifaqiah Islamic boarding school located in Indralaya, South Sumatra province, has implemented six Excellent classes based on memorizing the Koran. The formation of this Excellent class aims to produce a generation of Qur'anists who have a deep understanding of the contents of the Qur'an and become intellectuals who are proficient in various fields of general, exact and social sciences. The students in the Excellent class face various challenges during their education and learning period. Therefore, this research was conducted with the aim of evaluating and formulating strategies that can optimally improve the quality of learning. In this research, qualitative data measurements and analysis were carried out using a descriptive approach that explained in detail and was carried out through field research. Data collection and analysis was carried out through in-depth interviews, participant observation and document review. This research produces stages and steps for prevention and action against cases faced by students. Persuasive and cooperative approaches are prioritized in efforts to improve the quality of learning and teaching situations, as well as achieving Excellent class learning targets. From the evaluation results, it can be concluded that it is important to build a comfortable and focused learning system, so that it can create alumni who are competent in the fields of Tahfidz Al-Qur'an, religious sciences and general science.